Ion Gagim, USARB rector, dr. hab., writer (Confluenţe Bibliologice, 2017)
The article is dedicated to launching the books "Studies of Philosophy of Education" and "Musicological Studies" written by prof., dr. hab. Ion Gagim, rector of the "Alecu Russo" Balti State University. His experience of over 40 years in the field of education is presented: initiator and editor-in-chief of the culture, science and educational practice magazine “Arts and Art Education", author of school and university textbooks, school and university methodological guides, dictionaries, author of about 20 books in the field of education, culture, spirituality, philosophy, psychology, art and about 150 other publications in the country and abroad.
Keywords: Ion Gagim (1954); collection of the USARB Scientiﬁc Library; book launch